Downregulation of GPR183 on infection restricts the early infection and intracellular replication of mycobacterium tuberculosis in macrophage. (August 2020) - Tang, Jun; Shi, Ya'nan; Zhan, Lingjun; Qin, Chuan
Abstract: GPR183/EBI2 is a key chemotactic receptor for the positioning of B cells in lymphoid organs, and also for the migration of T cells and other immune cells. Here, we demonstrate that the downregulation of GPR183 in macrophage induced during Mtb infection restrains the bacterial early infection and intracellular replication. Overexpression of GPR183 or stimulation with its natural ligand favors Mtb replication in macrophage, while treatment with its antagonist represses both Mtb early infection and intracellular replication. With mutational analysis, we find that substitution of Asp-73, Arg-83, Tyr-112, Tyr-256 abolished the promotive effect of GPR183 on Mtb early infection and replication in macrophage. In conclusion, we demonstrated that beside the known role of chemotaxis receptor, GPR183 also functions directly in the interaction between macrophage and Mtb in a cell-autonomous way. Highlights: Downregulation of GPR183 in macrophage restrains Mtb early infection and replication. The antagonist NIBR189 represses Mtb early infection and replication. Key residue mutations could abolish the promotive effect of GPR183 on Mtb infection.